THE CONSTITUTIONAL INTERPRETATION OF WOMEN'S POLITICAL RIGHTS - Tanto Lailam; Nita Andrianti (Fakultas Hukum, Universitas Diponegoro, 2022)
The research focuses on the gender equality and justice interpretation of women's political rights in the Constitutional Court decisions. The problem is how does the interpretation of the constitution protect and fulfill women's political rights?. The research method is legal doctrinal, focusing on constitutional interpretation with several approaches, including the statutory, analytical, and case approaches. The result of the research shows that the function of the Court as a protector of women's political rights is a consequence of the existence of human rights in the 1945 Constitution. Its guarantees the constitutional review authority to protect human rights. Based on several decisions of the Court: affirmative action case, leadership positions in the house of representatives case, the women position of governor and vice governor's appointment in a Special Region of Yogyakarta. These decisions, which are above cases, are a form of protection and fulfillment of women's political rights in realizing gender equality and justice. Of course, it is motivated by the fact that women's representation must be present in every political decision-making in the national and local governance.